Hipertensión Arterial: una introducción general - Vidalón Fernández, Armando (2006)
Arterial hypertension represents an important public health problem, its prevalence dramatically increasing with age. In our country, a high percentage of the adult population has arterial hypertension with increased risk of cardiovascular disease. It forces us to seriously consider changes in our life style (physical activity and food habits) as well as the use of antihypertensive therapy in individuals for preventing serious complications of target organs. The goal of the current symposium is to improve knowledge on this disease.